Sex, power, conflict : evolutionary and feminist perspectives - Buss, David M.; Malamuth, Neil M. (OUP E-Books., 1996)
PART I: Evolutionary Perspectives. 1. Evolutionary Psychology and Marital Conflict, Martin Daly and Margo Wilson. 2. Power, Harassment, and Trophy Mates: The Feminist Advantages of an Evolutionary Perspective, Douglas T. Kenrick, Melanie R. Trost, and Virgil Sheets. 3. Sexual Harassment, Michael V. Studd. 4. Psychological Adaptation to Sexual Coercion in Victims and Offenders, Nancy Wilmsen Thornhill. PART II: Feminist Perspectives. 5. Where Are the Gender Differences? Where Are the Gender Similarities?, Janet Shibley Hyde. 6. Is Rape Sex or Violence? Conceptual Issues and Implications, Charle.